Effects of USDA quality grade and cooking on water-soluble precursors of beef flavor. (December 2018) - Dinh, T.T.N.; Legako, J.F.; Miller, M.F.; Brooks, JC.
Abstract: The objective of the current study was to determine the effects of three USDA quality grades and cooking on the water-soluble flavor precursors of beef Longissimus lumborum . Raw and cooked steaks from beef strip loins of USDA Prime (PR; n = 8), Low-Choice (LC; n = 8), and Standard (ST; n = 8) were analyzed for extractable free amino acids, reducing sugars, and other nitrogenous organic compounds (NOCs). Overall, two-way quality grade × cooking interactions were found for the contents of most water-soluble precursors ( P quality grade × cooking < 0.05), which were greater in raw LC and ST and were changed more in ST and LC steaks by cooking. The magnitude of those changes suggested that cystine, a dimer of cysteine, glucose, and glucose 6-phosphate might play more important roles in beef flavor development than previously thought. Highlights: Most water-soluble precursors of beef flavor occur more and are changed more by cooking in leaner beef. Cystine, glucose, and glucose 6-phosphate appeared to be more important for beef flavor than originally thought. Most non-amino acid nitrogenous organic compounds were decreased more by cooking in leaner beef.